ПОБУТ БУДІВЕЛЬНИКІВ ЗАПОРІЗЬКОГО ІНДУСТРІАЛЬНОГО КОМПЛЕКСУ (КІНЕЦЬ 20-х – ПОЧАТОК 30-х РОКІВ ХХ ст.) (Zaporizhzhia Historical Review, 2021)
This article analyses the material and living conditions of builders of Zaporizhzhya industrial complex during 20 – 30-s years of the XX-th century. The reasons of irregularity in medical service and providing of necessary goods for Dnepr building are defined.